Genotypic variation of flavonols and antioxidant capacity in broccoli - Duan, Yongbo; Eduardo Melo Santiago, Franklin; Rodrigues dos Reis, Andre [UNESP]; de Figueiredo, Marislaine A.; Zhou, Suping; Thannhauser, Theodore W.; Li, Li (Elsevier, 2021)
Flavonols are gaining increasing interests due to their diverse health benefits for humans. Broccoli is a main flavonol source in our diet, but the genetic variation of flavonols and their correlation with antioxidant capacity remain to be understood. Here, we examined variations of the two major flavonols kaempferol and quercetin in florets and leaves of 15 diverse broccoli accessions by ultra-performance liquid chromatography. Broccoli accumulated more kaempferol than quercetin in most of the accessions tested, with the ratios varying from 4.4 to 27.9 in leaves and 0.4 to 4.4 in florets. Total flavonoids showed 2.5-fold and 3.3-fold differences in leaves and florets of these accessions, respectively. Principle component analysis revealed that flavonols, along with the key biosynthetic pathway genes, correlated with antioxidant capacity related indicators. This study provides important information for broccoli flavonol genotypic variations and correlation with antioxidant capacity, and will facilitate the development of flavonol enriched cultivars in broccoli.
Keywords: Antioxidant capacity; Broccoli; Flavonol synthase gene; Flavonols; Kaempferol; Quercetin; Selenium